Trastuzumab versus observation for HER2 nonamplified early breast cancer with circulating tumor cells (EORTC 90091-10093, BIG 1-12, Treat CTC): a randomized phase II trial. (11th June 2018) - Ignatiadis, M; Litière, S; Rothe, F; Riethdorf, S; Proudhon, C; Fehm, T; Aalders, K; Forstbauer, H; Fasching, P A; Brain, E; Vuylsteke, P; Guardiola, E; et al.
Abstract: Background: Trastuzumab improves the outcome of women with HER2 positive breast cancer. We aimed to assess whether trastuzumab decreases the detection rate of circulating tumor cells (CTCs) in women with high risk, HER2 nonamplified, early breast cancer. Patients and methods: The EORTC 90091-10093 BIG 1– 12 Treat CTC is a phase II trial, conducted in 70 hospitals and 6 CTC laboratories across 5 European countries. Patients with centrally confirmed HER2 nonamplified breast cancer and ≥1 centrally confirmed CTC per 15 ml of blood by CellSearch ® following surgery and (neo)adjuvant chemotherapy were randomized (1 : 1) to 6 cycles of trastuzumab intravenously versus 18 weeks of observation. Randomization was stratified for center, locally confirmed estrogen receptor status and adjuvant versus neoadjuvant chemotherapy. The primary end point was rate of detection of ≥1 CTC per 15 ml of blood at week 18. Secondary end points were invasive disease-free survival (iDFS) and cardiac safety. Results: Between 30 April 2013 and 17 October 2016, 1317 patients were screened; 95 (7.2%) had detectable CTC(s), and 63 (4.8%) were randomized to trastuzumab ( n  = 31) or observation ( n  = 32). Fifty-eight patients were assessable for the primary end point, 29 in each arm. In 9 of the 58 patients, CTC(s) were still detected at week 18 : 5 in the trastuzumab and 4 in the observation arm (one-sided Fisher's exact test, P  = 0.765). An Independent Data Monitoring Committee recommended stopping further accrual for futility for the primary end point. Median follow-up at database lock was 13 months (IQR 4– 16.5). The 1-year iDFS was 93.8% (95% CI 77.3– 98.4) in the observation versus 84.8% (95% CI 63.4– 94.2) in the trastuzumab arm. No grade 2– 4 cardiac events were observed in the trastuzumab arm. Conclusion: Trastuzumab does not decrease the detection rate of CTCs in HER2 nonamplified, nonmetastatic breast cancer.